Characterization of Escherichia coli isolated from burn and chronic wound patients in Le Huu Trac National Burns Hospital - Vu, Thi Thu Loan; Nguyen, Thanh Viet (Tạp chí Y học Thảm hoạ và Bỏng, 2023)
Escherichia coli is responsible for many infections that affect burns and wound healing. They are highly resistant to antibiotics. Thus, the antimicrobial susceptibility pattern in burn and chronic wound infection may be useful in treating E. coli infections. This study aimed to determine the prevalence and the antibiotic susceptibility of E. coli in burn and chronic wound infection in the Le Huu Trac National Burns Hospital from January 2021 to May 2023. E. coli were identified and the antibiotics susceptibility testing was performed using the VITEK 2 automated system. A total of 4326 samples were cultured. There were 41 (0.95%) samples positive and 4285 (99.05%) samples negative for E. coli. The E. coli infected were more common in males (n = 22; 53.66%) than in female patients (n = 19, 46.34%). The infection was the highest in farmers (n = 25; 60.98%), followed by the self-employed (n = 8; 19.51%) and retired (n = 8; 19.51%). E. coli was highly sensitive to Fosfomycin (100%), Carbapenem class (> 90%), Colistin (92.31%), and Amikacin (87.18%) but resistant to Pefloxacin (100%), Minocycline (100%), Penicillins class (> 90%), and Trimethoprim-Sulfamethoxazole (84.62%). The use of Fosfomycin, carbapenem class, Colistin, and Amikacin are effective against E. coli and can help prevent the spread of infection.